We Want Black Students, Just Not You: How White Admissions Counselors Screen Black Prospective Students. Issue 4 (October 2019) - Thornhill, Ted
Most historically and predominantly white institutions (HPWIs) now desire some number of black students on their campuses. However, recent theoretical scholarship suggests that HPWIs' desire for and willingness to embrace black students is predicated on their racial palatability. The theory of intraracial discrimination stipulates that white gatekeepers are increasingly inclined to screen blacks to "weed out" those they perceive as too concerned with race and racism. In this study, the author assessed whether there was evidence of intraracial discrimination within the HPWI admissions regime. The data were derived through an audit of 517 white admissions counselors, employed at the same number of institutions, who received inquiry e-mails from fictitious black high school students who presented as more or less racially salient. The findings reveal that white admissions counselors are more responsive to black students who present as deracialized and racially apolitical than they are to those who evince a commitment to antiracism and racial justice. These findings provide convincing support for the theory of intraracial discrimination within the HPWI admissions regime. The author concludes with a brief discussion of the implications of these findings.